Application of Micro-Nanobubble Aeration in Spinach (Amaranthus viridis) and Pakchoi (Brassica rapa Chinensis) Cultivation with the Wick System - Elisabet Mutiara Hutabarat; Hilman Syaeful Alam; Asep Yusuf; Taufik Ibnu Salim; Norberta Yuni Rusmintia (The University of Lampung, 2023)
This study aimed to determine the effect of micro-nanobubble generator (MNBG) aeration on the cultivation of spinach (Amaranthus viridis) and pakchoi (Brassica rapa chinensis) hydroponic wicks. The basic principle of this system is that the axis capillary action flows nutrients to the planting medium. There are no moving parts so the nutrients can settle rapidly and the dissolved oxygen content is limited. Micro-nanobubbles (MNB) have the characteristics of a long residence time in the water so that their generation can operate intermittenttly. This study aims to determine the effect of applying (MNBG) with a flow rate of 0.98 L/minute on root length, plant height, and wet weight of spinach and pakchoi plants in wick hydroponics. Cultivation was hold on a free environment. There are three kinds of treatment; without aeration (N0), aeration 15 minutes x 4 for 24 hours (N15), and aeration 30 minutes x 4 for 24 hours (N30). Variations in the types of materials used in this study were spinach and pakchoi, as per treatment was repeat five samples. The study used a Randomized Block Design (RBD). The measurement results compared by the One-Way ANOVA test (5% level), then continued with Duncan's test to determine the difference. The results showed that there was an effect of applying intermittentt MNBG aeration on the average weight and height of the spinach plants, N15 treatment was more effective than the N0 and N30. Intermittentt MNBG aeration did not show a significant difference in the average weight of pakchoi. Keywords: Aeration, Hydroponics, Spinach, Pakchoi, wick